HUBUNGAN INTERAKSI TEMAN SEBAYA DENGAN KEPERCAYAAN DIRI ANAK USIA 5 – 6 TAHUN DI TK PERTIWI KOTA PEKANBARU - Eva Nita; Devi Risma; Zulkifli N Zulkifli N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The background of this research is the problem of self-confidence of children aged 5-6 years old in TK Pertiwi Kota Pekanbaru as there are children who look nervous when teacher asks to do activities, there are still children who have not been able to get along with their friends, children prefer to be spectators when they see their friends playing, there are children who are unable to think independently so they immediately ask for help from their teacher, there are still children who don’t dare to express their opinions. The purpose of this research is to know the correlation between peer interaction with self-confidence of children aged 5-6 years old in TK Periwi Kota Pekanbaru. The population of this research is 77 students 5-6 years old in TK Periwi Kota Pekanbaru. Because the number of the population is small, so all of them became the sample of the population. The method used in this research was quantitative correlation to know the correlation between peer interaction with self-confidence. The technique of collecting the data is observation. The technique of data analysis is using product moment correlation technique with SPSS for windows version 21 program. Based on the result of the hypothesis test there is a significant positive correlation between peer interaction with self-confidence of children aged 5-6 years old in TK Periwi Kota Pekanbaru. This can be known from the value of the correlation coefficient of rxy =0,682 and significance level 0,000<0,05. The level of correlation between peer interaction with self-confidence included in the strong category with the value of determinant coefficient is equal to KD = r² x 100% = 46,6%, it means that peer interaction gives effect of 46,6% to self-confidence.Key Word: Self-Confidence, Peer Interaction